Scavenging vibrational energy with a novel bistable electromagnetic energy harvester - Yan, Bo; Yu, Ning; Zhang, Lu; Ma, Hongye; Wu, Chuanyu; Wang, Ke; Zhou, Shengxi (Smart materials and structures, 2020)
Harvesting energy from mechanical vibrations via nonlinear energy harvesters has been considered as an effective approach for permanently powering embedded devices and sensors. Many previous studies focused on nonlinear piezoelectric energy harvesters based on cantilever beam structures. This paper presents a novel bistable electromagnetic energy harvester (BEEH) with several permanent magnets (PMs). The bistability is achieved by designing the interaction between magnetic repulsive and attractive forces. The shape of potential wells can be changed by adjusting the distance among the PMs. The theoretical model of the BEEH is established and the analytical solutions are obtained by using the harmonic balance method. The effects of the excitation frequency, excitation amplitude, resistance and shape of potential wells on the energy harvesting performance of the BEEH are investigated numerically and experimentally. The results show that the proposed BEEH has a wide operating bandwidth and high energy harvesting efficiency. The output power can reach up to 28 mW, which is able to power up some low-power consumption devices.